Towards a light-mediated gene therapy for the eye using caged ethinylestradiol and the inducible Cre/lox system - Kiy, Zoe; Chaud, Juliane; Xu, Liang; Brandhorst, Eric; Kamali, Tschackad; Vargas, Carolyn; Keller, Sandro; Hong, Huixiao; Specht, Alexandre; Cambridge, Sidney (Angewandte Chemie. International edition, 2024)
Increasingly, retinal pathologies are being treated with virus-mediated gene therapies. To be able to target viral transgene expression specifically to the pathological regions of the retina with light, we established an in vivo photoactivated gene expression paradigm for retinal tissue. Based on the inducible Cre/lox system, we discovered that ethinylestradiol is a suitable alternative to Tamoxifen as ethinylestradiol is more amenable to modification with photosensitive protecting compounds, i.e., “caging.” Identification of ethinylestradiol as a ligand for the mutated human estradiol receptor was supported by in silico binding studies showing the reduced binding of caged ethinylestradiol. Caged ethinylestradiol was injected into the eyes of double transgenic GFAP-CreERT2 mice with a Cre-dependent tdTomato reporter transgene followed by irradiation with light of 450 nm. Photoactivation significantly increased retinal tdTomato expression compared to controls. We thus demonstrated a first step towards the development of a targeted, light-mediated gene therapy for the eyes.
Gesehen am 18.03.2024
Online verfügbar: 21. Dezember 2023